(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to describe the status of reflective learning and related factors among nursing students. Participants and methods: A cross-sectional descriptive study was conducted with 360 nursing students at Dai Nam University. Results: Female students accounted for 82.5%; the mean age was 19.92 ± 1.12 years. The mean reflection in learning scale (RLS) score was 4.53 ± 1.01 on a 7-point Likert scale. The item “awareness of what I am learning and the purpose of learning” had the highest mean score (5.16 ± 1.23 points), whereas “integrating topics across courses/learning activities” had the lowest mean score (3.98 ± 1.35 points). Overall, 68.3% of students had a moderate level of reflection, 27.2% a good level, and 4.4% a poor level. Among subjective factors, attitude was the most prominent (3.36 ± 1.03 points); among objective factors, the most prominent was the managerial competence of leaders/lecturers (3.25 ± 1.09 points). Conclusion: Nursing students’ reflective learning was only at a moderate level, suggesting a need to strengthen structured reflective activities, particularly in learning planning and knowledge integration. In addition, greater lecturer support is needed to help students practice reflection more effectively.